Relational databases digital preservation - Freitas, Ricardo André Pereira (2009)
Digital preservation is emerging as an area of work and research that tries to provide answers that will ensure a continued and long-term access to information stored digitally. IT Platforms are constantly changing and evolving and nothing can guarantee the continuity of access to digital artifacts in their absence. This paper focuses on a speci c family of digital objects: Relational Databases; they are the most frequent type of databases used by organizations worldwide. A neutral format that is hardware and software independent is the key to achieve a standard format to use in digital preservation of relational databases. XML for its neutrality was chosen for this representation of the database. The presented solution o ers a possibility to achieve relational databases preservation. The prototype follows the "Reference Model for an Open Archival Information System" (OAIS).